Influence of Footing Shapes and GWT on Bearing Capacity and Settlement of Cohesive Soil Beneath Shallow Foundations - Khalid, M.; Sardar, A.; A. JAFFAR, S. T. (The Nucleus, 2020)
Footing shapes and ground water table (GWT) greatly affect the bearing capacity and settlement of cohesive soil. A series of laboratory experiments and simulation techniques are performed to investigate the effect of footing shapes and GWT on bearing capacity and settlement in cohesive soils. Results showed that by increasing the depth of footing, bearing capacity of cohesive soil increases while settlement and stress influence zone decreases. In case of square footing when depth of footing is increased from 1m to 2.2m bearing capacity also increased from 26.45kPa to 27.90kPa; while settlement and stress influence zone decreased from 0.30mm to 0.20mm and 1.2m to 0.60m, respectively. In case of rectangular footing when depth of footing is increased from 1m to 2.2m bearing capacity increased from 26.25kPa to 27.60kPa; while settlement and stress influence zone decreased from 0.60mm to 0.49mm and 1.53m to 1.15m, respectively. On the basis of high stress influence zone, critical footings are further selected to study the effect of GWT. It is observed that GWT does not affect the bearing capacity when its level is below the footing bottom, while settlement keeps on decreasing with the depth. A Soil Structure Interaction (SSI) model is proposed by comparing different built-in Finite Element Method (FEM) based models in Geo-5 software. Among the studied SSI models, Modified Elastic Model and Modified Mohr Coulomb Model proved to be more realistic models in terms of settlement, shear stress and effective stress